2016
DOI: 10.1002/aic.15149
|View full text |Cite
|
Sign up to set email alerts
|

Flow field during eccentric discharge from quasi‐two‐dimensional silos–extension of the kinematic model with validation

Abstract: A comprehensive investigation of granular discharge through the eccentric opening of rectangular silos has been presented. Slip flow of the grains over the vertical wall closer to the orifice was observed experimentally. This has not been emphasized by the earlier researchers. Considering slip flow at the wall, the kinematic model of granular discharge has been extended to simulate the hydrodynamics during drainage through any eccentric opening. The simulation is applicable over the entire range of eccentricit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…show, the velocity rises as the aperture widens for a given s. The asymmetry in the velocity profiles about the outlet center (x = 0) is evident, which reduces as s increases. The occurrence of non-zero slip velocity at the wall for s = 0 aligns well with the results reported by Maiti et al 11 . Further, as displayed in Figs.…”
Section: A Velocitysupporting
confidence: 92%
See 1 more Smart Citation
“…show, the velocity rises as the aperture widens for a given s. The asymmetry in the velocity profiles about the outlet center (x = 0) is evident, which reduces as s increases. The occurrence of non-zero slip velocity at the wall for s = 0 aligns well with the results reported by Maiti et al 11 . Further, as displayed in Figs.…”
Section: A Velocitysupporting
confidence: 92%
“…which is a edition of Eq. (11). For the data, all points within the orifice are taken into account except for s = 0, wherein the points located upto the Legend for all plots is given in (d).…”
Section: B Solid Fractionmentioning
confidence: 99%
“…The velocity distribution curve gradually flattens along the upward direction and eventually forms a plateau in the horizontal central zone, that is, a plug flow zone is formed in the upper part of the flowing zone. Such phenomenon has also been experimentally observed for funnel flow discharge 21–25 . Szabo et al 25 found the formation of plug flow zone was closely related to the particle shape.…”
Section: Resultssupporting
confidence: 52%
“…For funnel flow discharge, the flowing zone width first increases with vertical position and then keeps nearly constant 18–20 . Experimentally, it has been found that granular materials in the upper part of the flowing zone could be in plug flow state and notable velocity gradient only appears in the narrow shear region in between the flowing and stagnant zones 16,21–25 . Thus, if we consider the interface between flowing and stagnant zones as a rough surface, the flowing pattern of funnel flow is actually the same as that of mass/semi‐mass flow.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the flow fields of granular discharge in a two‐dimensional silo were investigated by Maiti et al The kinematic model of granular discharge was extended to simulate the hydrodynamics which was also validated by experiments and examined on its limitations. The mechanics of the arching was analyzed by Wang and Fan in the context of moving bed system during the continuous mass flow.…”
Section: Introductionmentioning
confidence: 99%